1990
DOI: 10.1289/ehp.9086143
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of epidemiologic studies on the human carcinogenicity of 1,3-butadiene.

Abstract: ,3-Butadiene, a major ingredient of synthetic rubber, has been shown to be carcinogenic in two animal species. To assess the possible human carcinogenicity of 1,3-butadiene, a critical review was undertaken of the epidemiologic literature.An early retrospective study of 8017 males employed in tire manufacturing found excess mortality for lymphatic and hematopoietic neoplasms in production workers (standardized mortality ratio, SMR = 560); these workers were exposed to 1,3-butadiene as well as to styrene and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…2 A cohort study in the United Kingdom of mortality among oil refinery workers, who would be expected to have higher exposures to these compounds than residential populations, has not shown an excess risk of leukaemia or other haematopoietic malignancy. 3 Few studies of cancer risks among residential populations living near to petrochemical industry have been reported.…”
mentioning
confidence: 99%
“…2 A cohort study in the United Kingdom of mortality among oil refinery workers, who would be expected to have higher exposures to these compounds than residential populations, has not shown an excess risk of leukaemia or other haematopoietic malignancy. 3 Few studies of cancer risks among residential populations living near to petrochemical industry have been reported.…”
mentioning
confidence: 99%
“…This reviewer noted the poor quality of exposure data available and the absence of any relationship between duration of employment or latency and lymphatic and hematopoietic cancer mortality risk. By contrast, a second reviewer (22) examined the same three studies and concluded that they strongly suggested an etiologic association between occupational exposure to I ,3-butadiene and human cancer, specifically lymphatic and hematopoietic cancer. The second reviewer noted that the excess mortality in the three studies tended to be greatest among production and maintenance workers and was absent for office staff.…”
mentioning
confidence: 99%
“…He also discounted the apparent inconsistency of subtypes of lymphatic and hematopoietic cancer reported in the different studies, citing evidence that indicates they may all derive from a common multipotential progenitor cell (23). Both reviewers (14,22) recommended that further efforts be made to quantify the butadiene exposures in the three cohorts, to permit firmer conclusions.…”
mentioning
confidence: 99%
“…A comprehensive review of 1,3-butadiene epidemiology is beyond the scope ofthis paper and is the topic of the succeeding two papers (4,5 …”
Section: Summary Of Findingsmentioning
confidence: 99%